Bibliometric Analysis of Toxic Leadership - Kencana, Yuga Arya (West Science Business and Management, 2025)
Leadership plays a central role in determining the success of an organization, both in terms of productivity and employee relations. However, not all leadership styles have positive effects. Toxic leadership is a type of disruptive leadership that causes emotional distress, reduces work motivation, and causes organizational dysfunction. This study aims to uncover research trends, collaboration patterns between authors and institutions, and important issues established over the last ten years by conducting a bibliographic analysis of recent studies on toxic leadership. This research approach processes data from Google Scholar according to the 2020–2025 requirements using VosViewer and Publish or Perish software. According to the study’s findings, counterproductive employee behaviour, high sales, and fewer organisational calls are all significantly impacted by toxic leadership. In order to establish a more wholesome and effective workplace, this study highlights how crucial it is for businesses to identify early toxic leadership tendencies and put ethical and emotional intelligence-based preventative measures into place.